SISTEM INFORMASI DALAM PELAYANAN LABORATORIUM - Benuriadi Benuriadi; Osman Sianipar; Guardian Yoki Sanjaya (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2012)
The development of information technology has altered the conventional type of hospital laboratoryservices, from mostly paper based into computerized system. In term of quicker and easier, the output of computer-based information is useful for the improving healthcare services management. Laboratory services in the public hospitals mostly used paper-based laboratory data processing, leading to problems of accessibility, usability, clarity and completeness of the information. This study aims to to know how to develop a computer-based laboratory information system for a supporting laboratory management in the hospital toward in depth and systematic assessment among relevant stakeholders. The study was conducted at Praya Public Hospital Central District of Lombok, Nusa Tenggara Barat. Five stages of prototyping method were used for the system development, namely: planning, designing, systems testing, pilot implementation and system evaluation. Data and information obtained to observe in this study were in-depth interviews and questionnaire dissemination. During the planning phase, there were four groups of information should be identified, which should be required by the hospital management, laboratory staff, physicians and other health providers and information for the patient as well. Following the need assessment, a context diagram, Data Flow Diagram (DFD), structure of database, Entity Relationship Diagram (ERD), input and output designs were created. A prototype of computer-based laboratory information system was developed according to these systematic analysis and design. Evaluation on user’s perception demonstrated that the prototype could provide laboratory information easily, understandable, as well as complete and useful for all group of users. In conclusion, developing information system that involved potential users in hospital laboratory unit demonstrated its usefulness and this encouraged that public hospitals should adopt computerized laboratory information systems.